Phytochemical Screening and Antibacterial activity of Polyphenol rich Extract of Passion Fruit Pericarp (Passiflora edulis Sims) on Propionibacterium acnes - Nugraha, Sony Eka; Syahputra , Rony Abdi; Nabila, Nabila (Talenta Publisher, 2023)
Indonesia's primary hub for cultivating purple passion fruit is North Sumatera. The passion fruit was transformed into a beverage product, which led to the creation of passion fruit pericarp trash. The potential medicinal properties of the passion fruit pericarp, particularly its antibacterial impact, need to be further explored. This study aimed to assess the phytochemical composition and antibacterial properties of an ethanol extract derived from the pericarp of purple passion fruit against Propionibacterium acnes. The extraction was performed using the percolation method with 96% ethanol. The antibacterial activity against Propionibacterium acnes was assessed using the agar diffusion method with paper discs. The phytochemical screening of the simplicia and ethanol extract revealed the existence of flavonoid, glycoside, saponin, tannin, and steroid/triterpenoid compounds. The ethanol extract exhibited significant antibacterial activity against Propionibacterium acnes at a dosage of 300 mg/ml, demonstrating a dose-dependent impact.